Women in Portuguese politics - Almeida, M. (Portuguese Journal of Social Science, 2009)
Has Portugal's transition to democracy since the 1974 revolution enhanced women's participation in politics? Has the democratisation process influenced women's access to elected offices? This paper offers an explanation of the Portuguese political system from a historical perspective, and an evaluation of the Portuguese political class in order to introduce the gender issue. Although the democratic regime is now more than 30 years old, there is still an under-representation of women in Portuguese politics, which is inscribed into the larger issue of women's access to all aspects of social, cultural and economic life. However, at all levels of government, women are better educated than men, with a larger proportion coming from the ranks of specialist professionals, teachers and top managers. Not surprisingly, left-wing parties recruit them in larger numbers.